The facts on file dictionary of biotechnology and genetic engineering - Steinberg, Mark L. (Mark L.); Cosloy, Sharon (New York : Facts on File, 1994)
Defines basic vocabulary of modern biotechnology and genetic engineering from A-DNA to zoo blot.
Book Report
Choice
Wilson's Senior High School
Adult.
Adult
Keywords: Biotechnology -- Dictionaries; Biotechnology -- Dictionaries; Genetic engineering -- Dictionaries; Genetic engineering -- Dictionaries